2020
DOI: 10.1155/2020/5245294
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation in Calca Promoter Inhibited ASC Osteogenic Differentiation in Rats with Type 2 Diabetic Mellitus

Abstract: The abnormal environment of type 2 diabetes mellitus (T2DM) leads to a substantial decrease in osteogenic function of stem cells. However, the gene sequence does not vary before and after disease for the patient. This phenomenon may be related to changes in osteogenesis-related gene expression caused by DNA methylation. In this study, we established T2DM models to extract adipose-derived stem cells (ASCs) for different gene identifications through DNA methylation sequencing. Specific fragments of methylation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…ADSCs were isolated from groin fat of young rats as previously described [ 43 ]. Adherent cells were cultured in a α-MEM medium with 10% FBS and 1% penicillin–streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…ADSCs were isolated from groin fat of young rats as previously described [ 43 ]. Adherent cells were cultured in a α-MEM medium with 10% FBS and 1% penicillin–streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Studies showed that adipose-derived stem cells (ASCs) in patients with type 2 diabetes mellitus (T2DM) caused upregulation of methylation level in promoter region of CALCA target fragment, resulting in a significant reduction in the osteogenic function of stem cells [ 35 ]. The above studies indicated that the abnormal methylation level of CALCA segments in stem cells may change the cell stemness on bone stem cells.…”
Section: Cgrp and Bone Stem Cellsmentioning
confidence: 99%
“…CpG island hypermethylation of CALCA occurs in juvenile mononuclear leukemia (JMML), regaining the hypermethylated phenotype upon relapse after treatment [ 161 ]. Thus, the abnormal methylation level of CALCA fragment in the promoter region of stem cells is an important reason for the change of cell stemness [ 35 ], and high-methylation phenotype is also an important biomarker in the process of tumor diagnosis and treatment.…”
Section: Cgrp and Tumor Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations